Clinical presentation and therapeutic outcomes of carnitine deficiency-induced cardiomyopathy - Fu, Li-jun (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2012)
OBJECTIVE: Carnitine deficiency has been associated with progressive cardiomyopathy due to compromised energy metabolism. The objective of this study was to investigate clinical features of carnitine deficiency-induced cardiomyopathy and the therapeutic efficacy of L-carnitine administration